(untitled) (European Journal of Education, 2020)
This study reveals the impact of Inquiry-based learning method with the 1st year students at MIST (Memorial International School of Tirana) and shows how this method of teaching can improve their learning. The aim of the study is to show the importance of Inquiry and present the main activities of teaching. To have a wider understanding about the topic, a survey was conducted about three months in one of the 1st classes of this school. The study was completed using primary data which were the questionnaires, book analysis, observations, and the secondary data which were books, articles and different websites. The study is focused on 1st year students and shows the impact of Inquiry based-learning on teaching English language. This study provides important information about teaching English. This method makes students more active, positive and independent in their learning.